Novel Heteroatom-Doped Fe/N/C Electrocatalysts With Superior Activities for Oxygen Reduction Reaction in Both Acid and Alkaline Solutions - Rauf, Muhammad; Wang, Jingwen; Iqbal, Waheed; Abbas, Mazhar; Khan, Sayed Ali; Khan, Qudrat Ullah; Ren, Xiangzhong; Zhang, Peixin; Li, Yongliang (Frontiers in Chemistry, 2020)
The exploration of noble metal-free catalysts with efficient electrochemical performance towards oxygen reduction reaction in the acid electrolyte is very important for the development of fuel cells technology. Novel pyrolyzed heteroatom-doped Fe/N/C catalysts have been regarded as the most efficient electrocatalytic materials for ORR due to their tunable electronic structure, distinctive chemical and physical features. Herein, nitrogen-doped Fe/N/C and sulphur-doped Fe/N/C-S electrocatalysts were synthesized using ferric chloride as the Fe precursor, N-rich polymer as N precursor and ketjen black EC-600 (KJ600) as the carbon supports. Among these electrocatalysts, the as-prepared sulphur and nitrogen-doped Fe/N/C-S reveals the paramount ORR activity with a positive half-wave potential value (E1/2) 0.82 at 0.80 V versus RHE in 0.1 mol/L H2SO4 solution, which is comparable to the commercial Pt/C (Pt 20 wt% ) electrocatalyst. The mass activity of the Fe/N/C-S catalyst can reach 45% (12.7A g-1 at 0.8 V) and 70% (5.3A g-1 at 0.95 V) of Pt/C electrocatalyst in acidic and alkaline solutions. As result, ORR activity of PGM-free electrocatalysts measured by the rotating-ring disk electrode method increases in the following array: Fe/N/C<Fe/N/C-S in both basic and acidic medium. This scientific work offers a facile approach to design and synthesize efficient heteroatoms-doped catalytic materials for electrochemical reactions in energy devices.